2015
DOI: 10.2337/db14-1098
|View full text |Cite
|
Sign up to set email alerts
|

Monounsaturated Fatty Acid–Enriched High-Fat Diets Impede Adipose NLRP3 Inflammasome–Mediated IL-1β Secretion and Insulin Resistance Despite Obesity

Abstract: Saturated fatty acid (SFA) high-fat diets (HFDs) enhance interleukin (IL)-1β–mediated adipose inflammation and insulin resistance. However, the mechanisms by which different fatty acids regulate IL-1β and the subsequent effects on adipose tissue biology and insulin sensitivity in vivo remain elusive. We hypothesized that the replacement of SFA for monounsaturated fatty acid (MUFA) in HFDs would reduce pro-IL-1β priming in adipose tissue and attenuate insulin resistance via MUFA-driven AMPK activation. MUFA-HFD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
212
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(227 citation statements)
references
References 26 publications
14
212
0
1
Order By: Relevance
“…It was found that the IL-1β, which is primed by high-fat diet (HFD) and is cleaved through the NLRP3 inflammasome complex [21,22], and which production in fat tissue is associated with the TLR4 receptor and nuclear factor-κB activation [23,24], directly influences the peripheral insulin resistance and type II diabetes [20,25,21,26,22]. In our study, glucose and insulin levels in blood serum, and HOMA insulin resistance index [16], as well as IL-1β and IL-12Br40 production were also increased in rats with MSG-induced obesity comparing with intact rats.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the IL-1β, which is primed by high-fat diet (HFD) and is cleaved through the NLRP3 inflammasome complex [21,22], and which production in fat tissue is associated with the TLR4 receptor and nuclear factor-κB activation [23,24], directly influences the peripheral insulin resistance and type II diabetes [20,25,21,26,22]. In our study, glucose and insulin levels in blood serum, and HOMA insulin resistance index [16], as well as IL-1β and IL-12Br40 production were also increased in rats with MSG-induced obesity comparing with intact rats.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, elevated levels of circulating FFAs were shown to activate the NLRP3 infl ammasome and weaken insulin sensitivity ( 27,28 ). In contrast, -3 FA ( 29 ) and MUFAs ( 30 ) have been shown to curtail NLRP3 Tanamoto ( 22 ), inhibition of proteasomal degradation by MG132 failed to rescue the ␥ T3-mediated decrease of TRAF6 or to increase K48-Ub of TRAF6 ( Fig. 6C ).…”
Section: Discussionmentioning
confidence: 95%
“…This effect of IVA337 might be due to PPARδ because it was previously shown that PPARδ activation decreases the expression of inflammasome components (NLRP3, caspase1, and IL‐1) when stimulated with palmitate (a saturated fatty acid) and lipopolysaccharides in hepatocytes 32. This effect could also be due to the PPARγ effect on SCD1 because saturated fatty acids activate the inflammasome whereas MUFAs inhibit the inflammasome components 26, 38. Overall, these results indicate that activation of PPARα, PPARδ, and PPARγ in the hepatocytes would contribute to the antisteatotic and anti‐inflammatory effect of IVA337 in the MCD and foz/foz models.…”
Section: Discussionmentioning
confidence: 98%